Paul Bunyan : the invention of an American legend - Van Sciver, Noah; Myles, Marlena, 1985- (TOON Graphics., 2023)
"In a humorous graphic novel set in Minnesota around 1914, we see W. B. Laughead, an advertising manager for a lumber company, spin the Paul Bunyan tall tales. Highlights the impact of clear-cutting old-growth forests. With contributions by Native authors as well as historical maps, photos, and a bibliography."